2020
DOI: 10.1136/bmjopen-2020-039200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight/obesity among the adult population in Ethiopia: a systematic review and meta-analysis

Abstract: BackgroundOverweight and obesity are emerging public health problems in Ethiopia. However, primary study findings on the prevalence of overweight and obesity in Ethiopia are inconsistent. Therefore, this study aimed to estimate the pooled prevalence of overweight and obesity among adults in Ethiopia.MethodsStudies that looked at overweight and obesity among adults were searched from four international databases. The search involved articles published from 1 January 2010 to 10 March 2020. The Cochran’s Q χ2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 51 publications
3
40
1
2
Order By: Relevance
“…39 Furthermore, the finding was also consistent with the findings of a systematic review and meta-analysis done among general population in Ethiopia that reported the prevalence of obesity to be 5.4% and overweight to be 20.4%. 40 Both developed and developing countries have reported an increasing prevalence of overweight and obese states in HIV-infected persons, consistent with trends in the general population. [41][42][43] Among those who are taking ART, under-nutrition has become less common and there is an increase in weight gain irrespective of ART regimen.…”
Section: Discussionsupporting
confidence: 58%
“…39 Furthermore, the finding was also consistent with the findings of a systematic review and meta-analysis done among general population in Ethiopia that reported the prevalence of obesity to be 5.4% and overweight to be 20.4%. 40 Both developed and developing countries have reported an increasing prevalence of overweight and obese states in HIV-infected persons, consistent with trends in the general population. [41][42][43] Among those who are taking ART, under-nutrition has become less common and there is an increase in weight gain irrespective of ART regimen.…”
Section: Discussionsupporting
confidence: 58%
“…The pooled prevalence of overweight and obesity among adult population in Ethiopia was 19% and obesity 5.4% respectively [ 30 ]. The current study intended to determine the prevalence of overweight/obesity and its determinants in adult patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Some literature in Ethiopia indicates overweight/obesity has emerged as a public health problem among adults in Ethiopia particularly in the urban areas [ 28 31 ]. However, there is limited literature on abdominal obesity in the Ethiopian context, despite its capacity as an indicator of the risk of different non-communicable diseases (NCDs) with waist circumference (WC) being morepredictive ofmetabolic syndromes, type 2 diabetes, and cardiovascular diseases than body mass index (BMI) [ 26 , 32 34 ].…”
Section: Introductionmentioning
confidence: 99%